2008
DOI: 10.1001/archotol.134.6.647
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Auditory Brainstem Response Results in Normal-Hearing Patients With and Without Tinnitus

Abstract: To evaluate electrophysiologically the auditory nerve and the auditory brainstem function of patients with tinnitus and normal-hearing thresholds using the auditory brainstem response (ABR).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
52
2
4

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 71 publications
(69 citation statements)
references
References 16 publications
10
52
2
4
Order By: Relevance
“…They are in agreement with previous reports of the following in tinnitus subjects: elevated V/I amplitude ratio (Kehrle et al 2008;Schaette and McAlpine 2011), elevated wave III amplitude (Attias et al 1996), and reduced wave I amplitude (Attias et al 1993;Schaette and McAlpine 2011). An absence of reduction in wave III of tinnitus subjects (Attias et al 1993) or wave V (Attias et al 1993; Schaette and McAlpine 2011), despite reduced wave I, has also been reported, which is tantamount to enhanced activity given the reduction in wave I (as discussed above).…”
Section: Comparison To Previous Abr Studies Of Tinnitussupporting
confidence: 93%
See 3 more Smart Citations
“…They are in agreement with previous reports of the following in tinnitus subjects: elevated V/I amplitude ratio (Kehrle et al 2008;Schaette and McAlpine 2011), elevated wave III amplitude (Attias et al 1996), and reduced wave I amplitude (Attias et al 1993;Schaette and McAlpine 2011). An absence of reduction in wave III of tinnitus subjects (Attias et al 1993) or wave V (Attias et al 1993; Schaette and McAlpine 2011), despite reduced wave I, has also been reported, which is tantamount to enhanced activity given the reduction in wave I (as discussed above).…”
Section: Comparison To Previous Abr Studies Of Tinnitussupporting
confidence: 93%
“…Although an earlier study by Attias et al (1993), also on subjects with highfrequency hearing loss, stated that there were no differences in ABR between tinnitus subjects and nontinnitus controls, the reported mean ABR amplitudes showed a clear trend toward reduced wave I. Kehrle et al (2008), comparing tinnitus and non-tinnitus subjects with clinically normal thresholds, reported an enhanced V/I amplitude ratio in tinnitus subjects. While they did not report whether the enhanced amplitude ratio arose from a reduction in wave I, an elevation in wave V or, a combination of both, the earlier data of Attias et al (1993) and recent report of Schaette and McAlpine (2011) indicate that reduced wave I was a factor.…”
Section: Introductionmentioning
confidence: 81%
See 2 more Smart Citations
“…In a study involving normal-hearing individuals, the authors concluded that the wave I extension and other BAEP wave delays are compatible with peripheral auditory lesions and can reflect hearing loss in ultra-high frequencies 21 -which were not assessed in the present study. In sensorineural hearing loss there can be an extension of wave I and its subsequent components, or reduction of the I-V interval, as well as wave I being absent, according to the level of loss.…”
Section: Discussioncontrasting
confidence: 56%